2015
DOI: 10.1088/0004-637x/803/1/9
|View full text |Cite
|
Sign up to set email alerts
|

HUBBLE SPACE TELESCOPEOBSERVATIONS OF THE NUV TRANSIT OF WASP-12b

Abstract: We present new observations of four closely-spaced NUV transits of the hot Jupiter-like exoplanet WASP-12b using HST/COS, significantly increasing the phase resolution of the observed NUV light curve relative to previous observations, while minimising the temporal variation of the system. We observe significant excess NUV absorption during the transit, with mean normalised in-transit fluxes of F norm 0.97, i.e. 2-5 σ deeper than the optical transit level of 0.986 for a uniform stellar disk (the exact confidenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 17 publications
5
53
1
Order By: Relevance
“…This suggests that whatever caused the early ingress in WASP-12b (Fossati et al 2010;Haswell et al 2012;Nichols et al 2015) was not from shocked stellar wind gas but is more likely planetary gas as has been previously suggested (Lanza 2009;Lai, Helling & van den Heuvel 2010;Bisikalo et al 2013a;Bisikalo et al 2013b;Cherenkov, Bisikalo & Kaigorodov 2014;Lanza 2015). An escaping atmosphere of WASP-12b would also explain the variability in the complete set of near-UV observations (Fossati et al 2010;Haswell et al 2012;Sing et al 2013;Nichols et al 2015). For the case of a hot (T ∼ 10 6 K) gas, we find that significant opacity (mainly metal lines) only appears for the ground-based near-UV wavelengths under unrealistic conditions of a nH above 10 10 cm −3 for the nominal model ( Figure 6).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This suggests that whatever caused the early ingress in WASP-12b (Fossati et al 2010;Haswell et al 2012;Nichols et al 2015) was not from shocked stellar wind gas but is more likely planetary gas as has been previously suggested (Lanza 2009;Lai, Helling & van den Heuvel 2010;Bisikalo et al 2013a;Bisikalo et al 2013b;Cherenkov, Bisikalo & Kaigorodov 2014;Lanza 2015). An escaping atmosphere of WASP-12b would also explain the variability in the complete set of near-UV observations (Fossati et al 2010;Haswell et al 2012;Sing et al 2013;Nichols et al 2015). For the case of a hot (T ∼ 10 6 K) gas, we find that significant opacity (mainly metal lines) only appears for the ground-based near-UV wavelengths under unrealistic conditions of a nH above 10 10 cm −3 for the nominal model ( Figure 6).…”
Section: Discussionsupporting
confidence: 52%
“…Additionally, Haswell et al (2012) observed an early ingress on WASP-12b in the NUVC (278.9 -282.9 nm) near-UV wavelength region caused by Mg II and the NUVA region using an additional 5 data points from COS on HST. Sequential HST COS observations of WASP-12b by Nichols et al (2015) combined the data from the NUVA, NUVB (265.5 -271.1 nm), and NUVC wavelength regions and also found an early ingress. The data from Haswell et al (2012) and Nichols et al (2015), however, are noisy.…”
Section: Introductionmentioning
confidence: 97%
“…Previous observations of an early ingress on WASP-12b and HD 189733b observe a flux drop difference of about ∼1 per cent and a timing difference of ∼>30 min between the near-UV and optical light curves (Fossati et al 2010;Haswell et al 2012;Ben-Jaffel & Ballester 2013;Nichols et al 2015). Both these properties are well within reach for ground-based metre-sized telescopes (e.g.…”
Section: Introductionsupporting
confidence: 58%
“…These observations can be subdivided into two groups: asymmetric and symmetric light curves. There are five exoplanets (55 Cnc b, GJ 436b, HD 189733b, HD 209458b, WASP12b) where asymmetries in their light curves are observed (VidalMadjar et al 2003(VidalMadjar et al , 2004(VidalMadjar et al , 2008(VidalMadjar et al , 2013Ben-Jaffel 2007Fossati et al 2010;Ehrenreich et al 2012Ehrenreich et al , 2015Haswell et al 2012;BenJaffel & Ballester 2013;Kulow et al 2014;Nichols et al 2015). For the symmetric transits, nine hot Jupiters (HAT-P-1b, HAT-P-12b, WASP43b, are observed to have a constant planetary radii from near-UV to optical wavelengths Turner et al 2013;Bento et al 2014;Nikolov et al 2014;Pearson, Turner & Sagan 2014;Mallonn et al 2015;Ricci et al 2015;Sing et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The latter hosts an inflated, short period hot Jupiter, which is subject to powerful mass-loss (Hebb et al 2009;Fossati et al 2010;Haswell et al 2012;Haswell 2017). Haswell et al (2012) and Fossati et al (2013) concluded that extrinsic absorption by material local to the WASP-12 system, and presumably escaping from the planet, is the most likely cause of the unexpected broad depression present at the cores of the Mg II h&k and Ca II H&K resonance lines (note that this depression is always present, regardless of the planet's orbital phase; Haswell et al 2012;Nichols et al 2015). General support to the idea that circumstellar material may be present around stars hosting close-in planets has been given by Cohen et al (2011), France et al (2013), Lanza (2014), Matsakos et al (2015), Fossati et al (2015c), Carroll-Nellenback et al (2016, and Staab et al (2017).…”
Section: Introductionmentioning
confidence: 99%